(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
. Antimicrobial resistance is a big problem that needs a healthy and serious care. The current study researches 39 staphylococcus isolated from urine of patients and outpatients and the antimicrobial resistance. The research carried out at the National Hospital in Qamishly during the period 2008 - 2009. Results showed that the rate of urinary tract infections was more in females (94.87%) than in males (5.12%) and more in adults (87.17%) than children (12.82%). We found that all the strains of isolated bacteria showed high susceptibility against Imipenem (94.82%), Cefazoline (83.84%), Ceftriaxone (69.23%), Cefaclor (69.2%), Amikacine (64.1%), and Gentamycine (61.5%). In addition, most isolated bacteria showed intermediate Sensitivity of Ciprofloxacin (53.8%), Levofloxacin (51.2%), and rate of sensitivity against Tobramicine (38.4%), Amoxicilline clavolanic acid (25.6%), Pefloxacine (25.6%), Vancomycine (25.6%). At the same time, most of the isolated bacteria showed resistance of Ceftazidime, Cefotaxime, Cefuroxim sodium, Ofloxacin, Cefoxitin, Sulphamethoxasole trimethoprim, Tetracyclines, Erythromycin, Penicillin, Ampicillin, Oxacillin, Amoxicilline. تعدّ إنتانات المسالك البولية لدى الرجال والنساء الناتجة عن جراثيم العنقوديات أحد أهم الإنتانات، وتبرز مقاومة الجراثيم للصادات الحيوية كمشكلة كبيرة ذات اهتمام صحي كبير، وتكمن خطورتها في ازدياد قدرة الجراثيم على تطوير وتغيير مقاومتها للصادات الحيوية. أُجريت هذه الدراسة على 39 عزلة من العنقوديات المعزولة من البول ومقاومتها للصادات الحيوية لدى المرضى المراجعين والمقيمين في المستشفى الوطني بالقامشلي في الفترة بين 2008 - 2009، وكانت النسبة المئوية للإنتانات في الإناث 94.87% أعلى مما هي عليه لدى الذكور 5.12%، والنسبة المئوية للإنتانات في البالغين 87.17% أعلى مما هي لدى الأطفال 12.82%، وأبدت هذه الجراثيم حساسية عالية تجاه كل من الإيميبينيم 94.82%، والسيفازولين 83.84%، والسيفترياكسون 69.23%، والسيفاكلور 69.2%، والأميكاسين 64.1%، والجنتاميسين 61.5%، وحساسية متوسطة للسيبروفلوكساسين 53.8%، والليفوفلوكساسين 51.2%، وحساسية بنسبة 38.4% للتوبراميسين، والأموكسيسيلين كلافولانيك أسيد 25.6%، والبيفلوكساسين 25.6%، والفانكوميسين 25.6%، ومقاومة للصادات الحيوية الآتية: السيفتازيديم، والسيفوتاكسيم، والسيفوروكسيم صوديوم، والأوفلوكساسين والسيفوكسيتين، والسلفاميثوكسازول تريميثوبريم، والتتراسيكلين، والإرثروميسين، والبنسيلين، والأمبيسيلين، والأوكساسيلين، والأموكسيسيلين